Concise Theology A Guide to Historic Christian Beliefs - Packer, J. I. (James Innell) (Wheaton, Ill. Tyndale House Publishers, Inc., 1993)
This guide to historic Christian beliefs, from one who is without a doubt one of the greatest living theologians, is an extremely apt summary of the Christian faith. Written in a lucid style, it does not embroil itself in theological controversies, but
Keywords: Theology, Doctrinal -- Popular works. Theology, Doctrinal -- Introductions. God -- Biblical teaching